Introduction to metal-ceramic technology, thrid edition - Naylor, W. Patrick ([S.l.] : Quintessence Publishing Co, Inc., 2019)
This is an introductory-level, skill-oriented technical guide to fabricating metal ceramic dental restorations. The book includes information on porcelain firing schedules, a list of suitable equipment, instruments and materials.
Introduction to metal-ceramic technology, thrid edition -- CONTENTS -- PREFACE -- Chapter 1: History and Overview -- Chapter 2: The Chemistry of Dental Porcelain -- Chapter 3: Casting Alloys for Bonding to Dental Porcelain -- Chapter 4: The Essentials of Metal-Ceramic Substructure Design -- Chapter 5: The Fundamentalsof Spruing, Investing, and Casting -- Chapter 6: How Does Dental Porcelain Bond to Metal? -- Chapter 7: Preparation of the Metal Substructure for Porcelain -- Chapter 8: Applying Dental Porcelain to the Metal Substructure -- Chapter 9: Adjusting and Finishing the Metal-Ceramic Restoration -- Chapter 10: The Porcelain-Margin Restoration -- Glossary of Technical Terms -- Appendix A: Materials Preferences and Trends -- Appendix B: Dental Porcelain Firing Schedules -- Appendix C: Celsius-Fahrenheit Conversion Chart -- Appendix D: Percentage Composition of Historical Metal-Ceramic Alloys -- Appendix E: Pre- and Postsolders for Metal-Ceramic Alloys -- Appendix F: Wax Pattern-Alloy Conversion Tables -- Appendix G: List of Equipment, Instruments, and Materials -- Index.
Includes bibliographical references and index.
Keywords: Metal Ceramic Alloys; Dental Porcelain; Technology, Dental